The influence of strength abilities on sports performance in climbing - Dosla, J.; Mesko, J. (Journal of Human Sport & Exercise, 2016)
The article discusses the influence of strength abilities on performance in climbing. Strength abilities were measured using two motor tests, test of dynamometry and pull-up hang test. We also measured selected anthropometric parameters (height, weight, body fat percentage and somatotype components - endomorphic, mesomorphic, ectomorphic). During the research a total of 46 persons have been measured; these were divided into three groups - performance climbers, recreational climbers and non-climbers. Only men have been included in the test. Statistically significant differences were found in parameters "pull-up hang" and "body fat percentage". No statistically significant differences between other parameters have been found. Average somatotype of the performance climbers was 2.03-4.87-2.98 which corresponds to the ectomorphic mesomorphy.